Do Lagged Terms Affect Exchange Rate Volatility in India? An Analysis Using ARIMA Model - Rai, Sushil Kumar; Sharma, Akhilesh Kumar (Indian Journal of Finance, 2022)
Under a flexible exchange rate regime, a stable exchange rate is considered a prerequisite condition to attract capital inflows into any economy. Consistency in the exchange rate has become a key objective of the economic policy of developing nations. However, more integration of financial markets under flexible exchange rate policy led to an increase in capital mobility affecting exchange rate volatility. This paper addressed the issue of variation in the exchange rate of the Indian rupee against the US dollar under a flexible regime using monthly data spanning from January 2005 to December 2020. By employing an autoregressive integrated moving average model, the study found that volatility in the exchange rate had the potential to affect the exchange rate for a duration of almost three years, which is quite a long duration. The study’s findings suggested that apart from other factors, the sharp changes in the exchange rate should be controlled by the economy because their effect will be reflected in the next period and thus create a chain event to bring further instability to the exchange rate.